Karakterisasi Enzim Pendegradasi AHL dari Bacillus cereus INT1c dan Bacillus sp. NTT3a - RATNANINGTYAS, SUSI; RUSMANA, IMAN; AKHDIYA, ALINA (Jurnal Sumberdaya Hayati, 2017)
Some of Gram-negative bacteria perform a phenomenon called quorum sensing (QS) to activate certain phenotypes such as pathogenicity. The bacterial cells performing QS produce N-acyl homoserine lactone (AHL) as signal molecules to communicate within a population. These molecules can be degraded by the enzyme, i.e. AHL lactonase. This study aimed to characterize the activity of AHL lactonase from Bacillus cereus INT1c and Bacillus sp. NTT3a in different pH and temperature levels. Both strains produce AHL-lactonase that could be found in intracellular and extracellular extracts. The dialysis process of extracellular AHL-lactonase of INT1c significantly increased the specific activity from 5.91 to 29.96, different from an extracellular enzyme of NTT3a that slightly increased from 4.08 to 5.39. Generally dialyzedAHL-lactonase of both B. cereus INT1c and Bacillus sp. NTT3a had activity in wide pH range with better activity in acidic pH and were not stable in high temperature with the highest activity at 30-40 oC.